Expert Validation of The Plant Herbarium Collection based on Local Wisdom of Sepasaran Bayi - Azim Zaimatul Ulya; Mucharommah Sartika Ami (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
The purpose of this study was to describe the results of the validation of herbarium experts and learning media experts on the herbarium collection of plants used in the traditional ceremony of Sepasaran Bayi in the Jombang Regency. This research is development research that refers to the R&D (Research and Development) model. The R&D model has ten stages, but only the first five stages were used in this study. The procedures carried out include: 1) potential and problems, 2) data collection, 3) product design, 4) design validation, and 5) design improvement. The potential and problem stages were carried out to collect information related to the potential of the Sepasaran Baby traditional ceremony in the Jombang Regency. The data collection stage was carried out to collect data on the types of plants used in the traditional ceremony through interviews with resource persons. The instrument is an interview guide. The third stage is the preparation of the herbarium design. The fourth stage is design validation by involving one herbarium expert and one learning media expert. The instrument used is a validation sheet. The fifth stage is design improvement, namely the improvement of the herbarium based on the assessment and suggestions of the two validators. Data analysis was done descriptively. The results showed that the herbarium was declared quite feasible by the herbarium expert with a percentage of 80.00% while the results of the validation of the learning media experts showed that the herbarium was declared very feasible with a percentage of 95.00%.